2021
DOI: 10.1097/bpo.0000000000001984
|View full text |Cite
|
Sign up to set email alerts
|

Minimum 2-Year Outcomes Following Arthroscopic Hip Labral Reconstruction in Adolescents and Young Adults

Abstract: Background: Labral repair is generally preferred when facing labral tears. When an irreparable labral tear in the context of femoroacetabular impingement syndrome is present, arthroscopic labral reconstruction has been proven to be a valid option for labral restoration. However, data on this procedure for the adolescent population is scarce. The purpose of the present study was to report minimum 2-year follow-up patient-reported outcome measures (PROMs) on adolescents and young adults following arthroscopic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, the average defect length or graft length was not reported; however, the Oxford hip score improved from 30 to 36 postoperatively and mean HOS improved from 59.5 to 79.3. Maldonado et al 36 reported outcomes for 28 adolescent hips (27 patients) undergoing reconstruction with semitendinosus allografts with a minimum 2-year follow-up. The authors initially used autografts but switched to allografts to reduce donor site morbidity.…”
Section: Allograft Optionsmentioning
confidence: 99%
“…Unfortunately, the average defect length or graft length was not reported; however, the Oxford hip score improved from 30 to 36 postoperatively and mean HOS improved from 59.5 to 79.3. Maldonado et al 36 reported outcomes for 28 adolescent hips (27 patients) undergoing reconstruction with semitendinosus allografts with a minimum 2-year follow-up. The authors initially used autografts but switched to allografts to reduce donor site morbidity.…”
Section: Allograft Optionsmentioning
confidence: 99%
“…11,30 Adolescents have demonstrated favorable short-, mid-, and long-term outcomes with durable improvements in PROs and low rates of revision. 26,30 Although adolescents undergoing primary hip arthroscopy have demonstrated significant improvement after hip arthroscopy, the mechanism of injury may influence reoperation rates. Ashberg et al 5 reported on adolescents who had acute onset from a discrete event of hip pain and demonstrated significantly higher reoperation rates compared with a matched group of adolescents with a chronic onset of injury.…”
mentioning
confidence: 99%
“…11,30 Adolescents have demonstrated favorable short-, mid-, and long-term outcomes with durable improvements in PROs and low rates of revision. 26,30…”
mentioning
confidence: 99%